55 readers for one copy - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
At the veterinary centre at Debre Marcos in Ethiopia, a lot of people use Teshome Muluye s copy of Spore. 'We circulate Spore in our office, and visitors come to our office to read it. About 15 veterinary workers, more than 20 agricultural field...